Chilean Adaptation and Validation of the Early Adolescent Temperament Questionnaire-Revised Version - Hoffmann, Marianela; Pérez, J. Carola; García, Catalina; Rojas, Graciela; Martínez, Vania (Frontiers in Psychology, 2017)
The aim of this study was to develop an adapted version of the Early Adolescent Temperament Questionnaire-Revised (EATQ-R) that would be valid and reliable for assessing temperament and its components in Chileans between 12 and 18 years of age. Originally, Ellis and Rothbart (2001) developed this questionnaire (EATQ-R) to be used in North American adolescents. For the study in Chile, a translation protocol was developed, to maintain the original instrument's cultural and linguistic equivalence in the adapted version. Psychometric properties of the EATQ-R, such as factor structure, internal consistency, and convergent validity, were also assessed. The adaption and validation was carried out in two stages, with two different studies. The first study, which included 612 adolescent students from educational establishments in the cities of Santiago and Concepcion, Chile, developed the Chilean version of the 83-item EATQ-R, which has 13 dimensions, belonging to 4 theoretical factors with adequate internal consistency (Cronbach's alpha = 0.79–0.82). The second study assessed the questionnaire's convergent validity, through its application to 973 adolescent students in Santiago. Results show that the effortful control subscale was significantly inversely related to indicators of adolescent maladjustment, such as substance abuse and behavioral problems. In addition, it was directly associated with indicators of self-concept, including self-esteem and self-efficacy. The opposite pattern was observed when considering negative affect. These findings coincide with current knowledge on the relationship between temperament and adjustment in adolescents.